Campaña publicitaria para el desarrollo socio ambiental para mejorar los métodos de uso y manejo de desechos en la Cdla. Primavera dos del cantón Durán en el 2016 - Llerena Tutivén, Bengie Belén (2016)
This research is part of the very worrying environmental situation which has several sectors of the canton Duran specifically the citadel spring Two; by the accumulation of waste in inappropriate places and which air is affected by different odors created by the decomposition of waste. Besides the visual pollution of cases opened by animals or by creating a contagious infectious chamberos community adds. This research is based on a quantitative model that is based on data taken in the sector such information he obtained through a questionnaire and the outcome of which determines the importance of the social and environmental development to improve the use and management of wastes proposed a program of specific activities on wastes generated from the home, which you can rescue certain wastes in order to improve the environment……